The urban racial state : managing race relations in American cities - Cazenave, Noel A., 1948- (Perspectives on a multiracial America series., 2011)
The Urban Racial State introduces a new multi-disciplinary analytical approach to urban racial politics that bridges urban theory, racism theory, and state theory by explaining the workings of the political structure whose urban governments enforce the regulation of race relations. In The Urban Racial State, Cazenave incorporates extensive archival and oral history case study data to support the placement of racism analysis at the center of the formulation of urban theory and the study of urban politics.